ETNOBOTANY STUDY ON THE UTILIZATION OF SIRIH TYPES (FAMILI: PIPERACEAE) IN KALIJAMBE VILLAGE, KECAMATAN BENER, PURWOREJO DISTRICT: STUDI ETNOBOTANI PEMANFAATAN JENIS-JENIS SIRIH (FAMILI: PIPERACEAE) DI DESA KALIJAMBE KECAMATAN BENER KABUPATEN PURWOREJO - Muhammad A'tourrohman; Malia Ulfah (Biocelebes, 2020)
Indonesia is known for its people who are rich in local wisdom and culture. Indonesian people have a lifestyle that likes to take advantage of plants. One type of plant that is widely used is betel-betel from the family Piperaceae. The purpose of this study is to examine the ethnobotany Piperaceae along with its morphology so that it can be used as information for the general public, especially the younger generation who are still confused about the different types of betel. This research was conducted in several stages, namely literature study, field observations, interviews, and data analysis. The method used is descriptive qualitative. Based on field observations, there are six types of betel vines that are known and utilized by the Kalijambe village community, namely P. betle, P. crocatum, P. nigrum, P. cubeba, P. sp., and P. retrofractum. The conclusion of this research is that there are six types of betel (Piperaceae) used by Kalijambe village community. Utilization of Piperaceae in the form of traditional medicines, food, economic value, ritual plants, and ornamental plants.